Effect of grape pre-drying and static pomace contact on physicochemical properties and sensory acceptance of Brazilian (Bordo and Isabel) red wines - Machado de Castilhos, Mauricio Bonatto [UNESP]; Conti-Silva, Ana Carolina [UNESP]; Bianchi, Vanildo Luiz Del [UNESP] (Springer, 2012)
Wine quality is evaluated by sensory attributes and physicochemical properties whose relationship is intensely investigated. This work aimed to analyze the physicochemical properties and sensory attributes of wines from Bord and Isabel American grapes elaborated by a traditional and two novel winemaking processes: pre-drying and submerged static pomace. It was possible to observe significant differences between the samples in all physicochemical properties (P < 0.001), except in volatile acidity. Bord and Isabel pre-drying wines presented the highest values of dry extract (43.00 and 33.66 g L-1) in comparison with the other wines which presented dry extract below 30 g L-1. Furthermore, pre-drying wines showed the highest phenolic content (1340.80 and 908.80 mg L-1) in comparison with static pomace (998.02 and 433.46 mg L-1) and traditional treatments (983.96 and 560.26 mg L-1). Sensory analysis showed significant differences between the samples in all attributes, except in appearance acceptance. Cluster analysis and multidimensional scaling was successfully applied and allowed to observe the relationship between physicochemical properties and sensory attributes. Total phenolic content and color indexes were associated with the appearance of wines, as well as alcohol content and acidity on aroma. The results also revealed the connection between dry extract and total and reducing sugars with the body of wines from innovative vinification. The flavor was associated with several physicochemical properties and also influenced the global acceptance of the samples. The innovative wines showed great acceptance in all sensory attributes, and the employment of these treatments on an industrial scale should be considered once providing wines with unique characteristics.
Keywords: Red wine; Novel winemaking; Vitis labrusca; Sensory evaluation; Chemical analysis